Gray Wolves in Washington: Possible Habitat and Corridors for Movement - Bisig, Joey (UW Tacoma Digital Commons, 2013)
Introduction:Increasing the Gray Wolf (Canis lupus) population in Washington state plays two important roles. First, they are an important part of many ecosystems as they are a keystone species. This means that they are a top predator and their absence has reverberating effects on the rest of the ecosystem. As seen at Yellowstone State Park in Wyoming, elk populations ran rampant for many years and reached their peak of roughly 25,000 individuals in 1988 (Kauffman et. al. 2008). The issue lies in the grazing that these elk partake in of a vital habitat producer, Aspen saplings. In 1995 thirty one Canadian Gray Wolves were released into Yellowstone in an attempt to reestablish the population and help curb ungulate populations (Larsen 2006). The park acts as a perfect ‘laboratory’ to monitor the effects wolves have on elk populations and on vegetation recovery levels. Second, Gray Wolves have been on the Washington Endangered Species list since 1967. This is attributed to the mass hunting and elimination of these animals that were largely perceived as nothing more than pests, mostly by owners of livestock. Washington State, as of December 2011, currently has a Gray Wolf population of twenty seven individuals and only three active breeding pairs (WDFW 2011 & Figure 1). The purpose of this study is to see if Washington has viable habitat for them and if so, how the Gray Wolves can move from each of these habitat islands. https://digitalcommons.tacoma.uw.edu/gis_projects/1052/thumbnail.jpg